2006
DOI: 10.1007/s11517-006-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT-based screening of biomechanical and structural properties of bone tissue engineering scaffolds

Abstract: The development of successful scaffolds for bone tissue engineering requires a concurrent engineering approach that combines different research fields. In order to limit in vivo experiments and reduce trial and error research, a scaffold screening technique has been developed. In this protocol seven structural and three biomechanical properties of potential scaffold materials are quantified and compared to the desired values. The property assessment is done on computer models of the scaffolds, and these models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 30 publications
1
60
0
Order By: Relevance
“…22,23 For this work, pore size (1 mm), pore shape (spherical), and pore interconnectivity (100%) were kept constant between the two permeability designs (high and low). Variation in permeability was created through changing the amount of overlap between spherical pores, which resulted in differences in porosity, throat size, and surface area, as these design features are interrelated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 For this work, pore size (1 mm), pore shape (spherical), and pore interconnectivity (100%) were kept constant between the two permeability designs (high and low). Variation in permeability was created through changing the amount of overlap between spherical pores, which resulted in differences in porosity, throat size, and surface area, as these design features are interrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies (described below) demonstrate that pore size, interconnectivity, and porosity affect bone tissue regeneration, and these three design features appear to be the most important structural variables in an initial scaffold screening algorithm developed by Cleyenbreugel et al 22 for bone tissue engineering applications. It is difficult to keep all three of these variables constant and create two scaffolds of differing permeability that can be built successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Cahill et al found that models based on the designed scaffold geometry over-predicted the scaffold stiffness by up to 147% and that surface roughness is a factor that needs to be accounted for 4 . High resolution finite element meshes have been successfully generated from micro-CT scans giving accurate models of the real geometries of both bone tissue engineering scaffolds 6,10,38,49,50,52,57 and native bone tissue 2,29,40,47,51 .Micromechanics approaches to evaluate the mechanical properties of particle-reinforced composites traditionally use idealised microstructures based on particle distribution and are often modelled under periodic boundary conditions 5 . This approach was used by Eshragi et al to determine the bulk mechanical properties of a PCL/hydroxyapatite SLS scaffold 14 .…”
mentioning
confidence: 99%
“…Such analysis can be used to vary several geometrical or material parameters at the same time and to choose the most suitable ones for the replacement of natural tissues [7]. Simulations of perfusion bioreactors have been investigated for 3D scaffold performances [10], [11], [12]. Lacroix, D., and Prendergast, P.J.…”
Section: Introductionmentioning
confidence: 99%